Ecological assessment of heavy metals accumulation in sediments and leaves of Avicennia marina along the Diu coast of the northeast Arabian Sea - Varsha Patale; Jigna G. Tank (Oceanologia, 2022)
The Coastal region of Diu is the natural habitat dominated by Avicennia marina mangrove species at the southeast coast of Saurashtra in Gujarat state of India. However, Diu being a famous industrial and tourism place survival of these mangrove species is threatened due to anthropogenic activities. In present studies, sediment and leaf samples of A. marina were collected from the Diu coast to evaluate the ecological threat of heavy metals accumulation in the marine habitat. There was remarkable presence of heavy metals such as copper, nickel, cadmium, chromium and lead in sediments and leaf samples of A. marina. The values of Biological concentration factors (BCFs) of heavy metals in leaf samples were high for cadmium, chromium and lead which suggest chelation of these heavy metals with biomolecules. The geo-accumulation index suggested that Site-4 and Site-5 were heavily contaminated with copper and nickel. The ecological risk index suggested that there is no significant effect of heavy metals on growth of plants in the mangrove ecosystem. Principal component analysis revealed that the samples collected from the natural habitats (Site-4 and Site-5) near the fishing and industrial areas were the main sources of heavy metal contamination. Hence, it was concluded that the concentration of heavy metals in the studied ecosystem had limited impact on growth of plants at Site-1, Site-2 and Site-3. However, growth of plants at Site-4 and Site-5 were threatened due to the toxic effect of copper and nickel present in its sediments.